LINGUISTIC ANALYSIS OF PHRASEOLOGICAL UNITS WITH ANTONYM COMPONENTS IN ENGLISH, UZBEK AND RUSSIAN - Samadova Visola Baxtiyor qizi (Western European Studies, 2025)
Phraseological Units (PUs): Fixed expressions in a language whose meanings are not deducible from individual word meanings. Common types include idioms, proverbs, and collocations. Antonymic PUs: These are phraseological units containing contrasting components, representing opposing ideas or concepts (e.g., "a blessing in disguise" vs. "a curse in disguise"). Cultural Reflection: Antonymic PUs reflect cultural values. In English and Uzbek, opposites often convey differing societal attitudes toward success, failure, fortune, and misfortune. Structure: Antonymic PUs usually consist of two contrasting parts. They follow a syntactic pattern where one idea is countered by its opposite (e.g., "better safe than sorry" vs. "fortune favors the bold"). Psychological Impact: These units evoke contrasting emotions such as hope vs. despair, success vs. failure, highlighting the psychological and emotional states of speakers.
Keywords: Antonymic Phraseological Units; Linguistic Duality; Cultural Idioms